2018
DOI: 10.20961/shes.v1i1.23656
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Learning Model Picture and Picture and Reading Interest Toward Students’ Poetry Writing Skills of 5th Grade Primary School Students

Abstract: <em>The study </em><em>aims to know the effect of Picture and Picture learning model and reading intertest toward poetry writing skills. The study </em> <em>used quasi experimental type of quantitative approach with Anova two-way analysis of variance</em><em>. The samples were taken by using cluster random sampling. The data were collected by doing test. The instrument was tested using factor analysis. The data were analyzed using descriptive analysis and statistical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…It meant that the picture and picture learning model increased the learners' ability in writing. The finding was in agreement with the previous studies (Sarifah & Apsari, 2020;Shanorra et al, 2021;Mulyani et al, 2018;Hidayatullah, 2022;Audina et al, 2018;Tarigan et al, 2021;Muchtar et al, 2020) which found that the picture and picture learning model could improve the students' writing ability.…”
Section: Results Of Writing Tests For Control Croup Pre-testsupporting
confidence: 93%
“…It meant that the picture and picture learning model increased the learners' ability in writing. The finding was in agreement with the previous studies (Sarifah & Apsari, 2020;Shanorra et al, 2021;Mulyani et al, 2018;Hidayatullah, 2022;Audina et al, 2018;Tarigan et al, 2021;Muchtar et al, 2020) which found that the picture and picture learning model could improve the students' writing ability.…”
Section: Results Of Writing Tests For Control Croup Pre-testsupporting
confidence: 93%
“…Next, a research conducted by Audina et al, (2018)This study aims to 1) find out the differences poetry writing skills among students who are taught by the picture and picture learning model and the concept sentence learning model; 2) knowing the differences in poetry writing skills between students who have high reading interest and low reading interest; and 3) knowing the interaction of learning models and reading interest on poetry writing skills. This study used a quasi-experimental research method with a 2 x 2 factorial design.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been conducted on the use of the Picture and Picture model. Research on the use of the Picture and Picture model in Indonesia by Handayani, Bintari, and Lisdiana (2013), Audina, Slamet, and Poerwanti (2018), Ekawati, Bella, and Firmansyah (2019). Therefore, the author wants to conduct research on the development of thematic teaching materials based on the picture and picture model.…”
Section: Introductionmentioning
confidence: 99%